Homelessness and housing advocacy the role of red-tape warriors - Smith, Curtis (Routledge, Taylor & Francis Group, 2022)
"Through compelling ethnography, Homelessness and Housing Advocacy: The Role of Red-Tape Warriors reveals the creative and ambitious methods that social service providers use to house their clients despite the conflictual conditions posed by the policies and institutions that govern the housing process. Combining in-depth interviews, extensive fieldwork and the author's own professional experience, this book considers the perspective of social service providers who work with the homeless and chronicles the steps they take to navigate the housing process. With assertive methods of worker-client advocacy at the center of its focus, the book beckons attention to the many variables that affect professional attempts to house homeless populations. It conveys the challenges that social service providers encounter while fitting their clients into the criteria for housing eligibility, the opposition they receive, and the innovative approaches they ultimately take to optimize housing placements for their clients who are, or were formerly, experiencing homelessness. Weaving as it does between issues of poverty, social inequality, and social policy, Homelessness and Housing Advocacy will appeal to courses in social work, sociology, and public policy and fill a void for early-career professionals in housing and community services"--
Keywords: Sozialdienst; Verwaltungsvereinfachung; Wohnungspolitik; Obdachlosigkeit; Social service; Homelessness; Housing policy; Social work administration; Social Work; Service social; Itinérance; Logement / Politique gouvernementale; Service social / Gestion; homelessness